2018
DOI: 10.7717/peerj.4661
|View full text |Cite
|
Sign up to set email alerts
|

Replication study: androgen receptor splice variants determine taxane sensitivity in prostate cancer

Abstract: In 2015, as part of the Prostate Cancer Foundation–Movember Foundation Reproducibility Initiative, we published a Registered Report (Shan et al., 2015) that described how we intended to replicate selected experiments from the paper “Androgen Receptor Splice Variants Determine Taxane Sensitivity in Prostate Cancer” (Thadani-Mulero et al., 2014). Here we report the results of those experiments. Growth of tumor xenografts from two prostate cancer xenograft lines, LuCaP 86.2, which expresses wild-type androgen rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A recent study suggested that AR splice variants may also affect sensitivity to taxanes and that tumors predominantly expressing the ARv7 variant, associated with ADT resistance, would also likely be resistant to DTX [ 47 ]. However, an independent group was unable to replicate these results under similar experimental conditions [ 48 ]. Furthermore, another group found that detection of ARv7 in circulating tumor cells of mCRPC patients was not associated with taxane-resistance and that certain patients with ARv7-positive status at baseline converted to ARv7-negative status during the course of taxane therapy, adding uncertainty to the clinical significance of this variant in patients receiving taxanes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that AR splice variants may also affect sensitivity to taxanes and that tumors predominantly expressing the ARv7 variant, associated with ADT resistance, would also likely be resistant to DTX [ 47 ]. However, an independent group was unable to replicate these results under similar experimental conditions [ 48 ]. Furthermore, another group found that detection of ARv7 in circulating tumor cells of mCRPC patients was not associated with taxane-resistance and that certain patients with ARv7-positive status at baseline converted to ARv7-negative status during the course of taxane therapy, adding uncertainty to the clinical significance of this variant in patients receiving taxanes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, ~1 out of 5 men will be diagnosed with PCa (4), while in China, the incidence of PCa is 7.1/100,000 individuals (7). Although PCa has a 5-year survival rate of 98.6% (4,8), an in-depth understanding of its pathogenesis and new therapeutic strategies are still urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that AR-V7 expressing tumor xenografts were resistant to docetaxel therapy while ARV567es expressing xenografts were highly sensitive to docetaxel. Of note, these results were unable to be independently replicated by a second group in the same xenograft models [37] . Zhang et al.…”
Section: The Ar Variantsmentioning
confidence: 85%